State Recognition as a Maritime Security Strategy: Israel’s Recognition of Somaliland in the Red Sea Crisis - Muhammad Adnan Nurcahyo; Pierre Canry Rambe Manalu (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2026)
This study examines Israel’s recognition of Somaliland in the context of maritime insecurity in the Red Sea during 2023–2026. The research addresses how and why state recognition can function as a strategic instrument for maritime security. The study aims to identify the strategic interests Israel seeks to secure, assess Somaliland’s geopolitical value, and analyze the regional security implications of the recognition. The analysis applies Neorealism and Regional Security Complex Theory to explain the interaction between structural pressures and regional security dynamics. The research employs a qualitative case study design based on document analysis of institutional reports, policy documents, and scholarly literature. The findings indicate that Israel’s recognition of Somaliland serves as a strategic response to maritime vulnerabilities around the Bab el-Mandeb chokepoint by expanding potential access to strategic infrastructure such as Berbera Port. However, this move also triggers regional securitization related to territorial integrity and alters the security configuration of the Red Sea region.